Evaluation of the Mini-ridge Filter’s Impact on the Generation of Secondary Radiation in Synchrotron-based Proton Beam Therapy - Takahiro Shimo; Shintaro Shiba; Hiroyuki Watanabe; Masashi Yamanaka; Kazuki Matsumoto; Akihiro Yamano; Kohichi Tokuuye (Journal of Medical Physics)
Purpose: This study evaluated whether the mini-ridge filter (MRF) used for beam energy optimization in a synchrotron-based proton beam therapy (PBT) affects the generation of secondary neutrons and photons. Materials and Methods: Secondary radiation from the PBT was evaluated using a Monte Carlo simulation (MCS) with the Particle and Heavy-ion Transport code System (version 3.31), and the PROBEAT-M1 system (Hitachi, Japan) was modeled. In the analysis, we focused on the production of neutrons and photons in a 35 cm ×35 cm ×35 cm water phantom with and without MRF to ensure the accuracy of the dose calculation. Results: The MCS results were in good agreement with the measurement results, and the off-axis ratio at the center of the spread-out Bragg peak was 100% at a gamma analysis pass rate of 2 mm/2%. The photon fluence decreased by 4.0 and 0.9% at 70.2 and 228.7 MeV, respectively, but no significant effect on total neutron and photon production was observed (P > 0.05). The MRF effect on the dose was <0.11 μGy Gy−1, suggesting that a clinically significant effect is negligible. Conclusions: These results demonstrated that MRF had a limited effect on the generation of secondary radiation in PBT. MRF, which is used to improve dose distribution, has the potential to be safely used without increasing secondary radiation, and MRF might not affected to generate secondary radiation to clinically meaningful levels.